Human on fire as a gesture of self-offering in Polish documentary films - Tes , Urszula (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Tes Urszula, Human on fire as a gesture of self-offering in Polish documentary films “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 172–179. ISSN 1731-450X. DOI 10.14746/i.2019.34.12. One of strongest acts of personal protest in the communist era was self-immolation, which was the subject of two Polish documentaries. Maciej Drygas in Hear My Cry invoked the figure of Ryszard Siwiec, who immolated himself on September 8, 1968 as a sign of protest against the Soviet army invasion of Czechoslovakia. In his documentary, Drygas shows a fragment of the film with the burning man, juxtaposing it with the testimony of witnesses to the tragedy and the account of the family. This documentary restores the memory of the whole society, who due solely to the film, learned about the radical gesture of a common man. Holy Fire by Jarosław Mańka and Maciej Grabysa in turn invokes the heroic but forgotten Walenty Badylak, who immolated himself in March of 1980 in Cracow as an expression of his objection to distortion of the truth about Katyń. Both acts of self-immolation had for many years been perceived as totally futile acts, while the directors show that the self-immolation of these now has a deep and symbolic meaning. In my analysis, I shall invoke historic and cultural contexts, conduct a multifaceted interpretation of self-immolation act and discuss the complex imagery included in the films.